2007
DOI: 10.1590/s0102-261x2007000600009
|View full text |Cite
|
Sign up to set email alerts
|

Terdiurnal tides in the MLT region over Cachoeira Paulista (22.7ºS; 45ºW)

Abstract: Five years of winds measurements obtained by a SkiYmet meteor radar at Cachoeira Paulista (22.7 • S, 45.0 • W) are used to investigate the terdiurnal tide. This type of tide is frequently observed in the meteor region but the mechanisms responsible for its production are not yet completely explained. Among the possible causes are solar direct forcing and nonlinear interactions between the diurnal and semidiurnal tides. Nonlinear interaction between diurnal and semidiurnal tides can generate two secondary waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The meridional component of Maui 8-h tide exhibits semiannual variations similar to those observed at Cachoeira Paulista (22.7 • S, 45 • W), a low-latitude station in the Southern Hemisphere (Tokumoto et al, 2007). The 8-h tides at both sites peak near the equinoxes and at higher altitudes.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The meridional component of Maui 8-h tide exhibits semiannual variations similar to those observed at Cachoeira Paulista (22.7 • S, 45 • W), a low-latitude station in the Southern Hemisphere (Tokumoto et al, 2007). The 8-h tides at both sites peak near the equinoxes and at higher altitudes.…”
Section: Discussionsupporting
confidence: 63%
“…The vertical wavelength reported by the previous studies was found to vary widely, over a range from 12 to more than 1000 km. At high-latitude, 68 • N, the vertical wavelength was from 31 km to 91 km (Younger et al, 2002); at mid-latitudes, ∼43-52 • N, the vertical wavelength varied in a large range from 22 to ≥1000 km (Thayaparan, 1997;Namboothiri et al, 2004); and at the low latitude of 22 • S shorter vertical wavelengths ∼12-32 km in the meridional wind were reported by Tokumoto et al (2007).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations